Positive electrode for non-aqueous electrolyte power storage element, and non
By using a metal aluminum substrate and a thin layer of positive electrode active material in the positive electrode of the nonaqueous electrolyte power storage element and increasing the pressing pressure, the problem of the positive electrode being snaked under high pressure is solved, and the effect of high-pass foil properties and low defect rate is achieved.
Patent Information
- Application Number
- CN202380063018.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-26
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-11
AI Technical Summary
The positive electrode of the nonaqueous electrolyte power storage element manufactured under high pressure is prone to snake, resulting in a larger offset of the positive electrode position of the winding electrode body, and a tendency for an increase in the defect rate.
A positive electrode substrate containing metal aluminum is used, the average thickness of the positive electrode active material layer is less than 35 μm and the peel strength of 180° is 0.6 N/mm or more, and the pressing pressure is increased during the manufacturing process to suppress peeling of the positive electrode active material layer.
The peeling of the positive electrode active material layer is effectively suppressed, the foiling property is improved, the defect rate in the winding process is reduced, and the overall performance of the non-aqueous electrolyte power storage element is improved.
Smart Images

Figure CN119816949A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode for a nonaqueous electrolyte energy storage device and a nonaqueous electrolyte energy storage device. Background Art
[0002] Non-aqueous electrolyte secondary batteries represented by lithium ion secondary batteries are mostly used in electronic devices such as personal computers, communication terminals, and automobiles due to their high energy density. The above-mentioned non-aqueous electrolyte secondary batteries are generally composed of a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte between the electrodes, and are charged and discharged by performing charge transfer ions between the two electrodes. In addition, as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and double electric layer capacitors have also been widely popularized.
[0003] The positive electrode used in the non-aqueous electrolyte storage element generally has a structure in which a positive electrode active material layer is stacked on a positive electrode substrate. As the positive electrode substrate, a foil made of metal aluminum is widely used from the viewpoint of high conductivity, etc. (see Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-201589 Summary of the invention
[0007] Usually, when manufacturing the positive electrode, the positive electrode active material layer is formed by coating the positive electrode mixture paste on the positive electrode substrate and drying it, and then the positive electrode active material layer is pressed relative to the positive electrode active material layer by a pressing device such as a roller press. Then, the obtained positive electrode and negative electrode are wound in an overlapping state via a separator, thereby making a wound electrode body. Here, in order to suppress the peeling of the positive electrode active material layer during the manufacturing process of the electrode body, it is ideal to press the positive electrode during the manufacturing process under high pressure so that the positive electrode active material layer and the positive electrode substrate are firmly in close contact. However, the inventors and others found that the positive electrode obtained by pressing under high pressure is prone to meandering when supplied to the winding device (hereinafter, the situation where it is easy to meander when supplied to the winding device is referred to as "low foil passability", and the situation where it is not easy to meander is referred to as "high foil passability"). When using such a positive electrode with low foil passability, the positional offset of the positive electrode in the width direction of the obtained wound electrode body becomes larger, and there is a tendency for the defective rate to increase.
[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a positive electrode for a nonaqueous electrolyte power storage device in which the peeling of a positive electrode active material layer is suppressed and the foil permeability is high, and a nonaqueous electrolyte power storage device including such a positive electrode.
[0009] One aspect of the present invention relates to a positive electrode for a non-aqueous electrolyte storage element (hereinafter also referred to as a "positive electrode") comprising a positive electrode substrate containing metallic aluminum and a positive electrode active material layer stacked on the positive electrode substrate, wherein the positive electrode substrate has an elongation at break of less than 3.8%, an average thickness of the positive electrode active material layer of less than 35 μm, and a 180° peel strength between the positive electrode active material layer and the positive electrode substrate of greater than 0.6 N / mm.
[0010] A nonaqueous electrolyte electricity storage device according to another aspect of the present invention includes the positive electrode according to one aspect of the present invention.
[0011] According to one aspect of the present invention, there can be provided a positive electrode for a nonaqueous electrolyte electricity storage device in which peeling of a positive electrode active material layer is suppressed and foil permeability is high, and a nonaqueous electrolyte electricity storage device including such a positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a perspective view showing one embodiment of a non-aqueous electrolyte electricity storage element.
[0013] Figure 2 This is a schematic diagram showing one embodiment of an electricity storage device constituted by assembling a plurality of nonaqueous electrolyte electricity storage elements.
[0014] Figure 3 This is a graph showing the relationship between the elongation at break of the positive electrode substrate and the number of defects in the winding step. DETAILED DESCRIPTION
[0015] It can be understood from the following description and examples that the contents disclosed in this specification include the following contents.
[0016] [1] A positive electrode for a non-aqueous electrolyte storage element, comprising a positive electrode substrate and a positive electrode active material layer, wherein the positive electrode substrate contains metal aluminum and the positive electrode active material layer is stacked on the positive electrode substrate;
[0017] The elongation at break of the positive electrode substrate is 3.8% or less.
[0018] The average thickness of the positive electrode active material layer is 35 μm or less.
[0019] The 180° peel strength between the positive electrode active material layer and the positive electrode substrate is 0.6 N / mm or more.
[0020] [2]: The positive electrode according to [1] above, wherein the average thickness is 80 μm or less.
[0021] [3]: The positive electrode according to [1] or [2] above, wherein the density of the positive electrode active material layer is 2.6 g / cm3 above.
[0022] [4]: A non-aqueous electrolyte energy storage device comprising the positive electrode according to any one of [1] to [3] above.
[0023] First, the outlines of the positive electrode for the nonaqueous electrolyte electricity storage device and the nonaqueous electrolyte electricity storage device disclosed in this specification are described.
[0024] [1] One aspect of the present invention relates to a positive electrode for a non-aqueous electrolyte storage element, comprising a positive electrode substrate containing metallic aluminum and a positive electrode active material layer stacked on the positive electrode substrate, wherein the elongation at break of the positive electrode substrate is 3.8% or less, the average thickness of the positive electrode active material layer is 35 μm or less, and the 180° peel strength between the positive electrode active material layer and the positive electrode substrate is 0.6 N / mm or more.
[0025] In the positive electrode described in [1] above, the peeling of the positive electrode active material layer is suppressed and the foil permeability is high. The reason for the above effect is still uncertain, but it is speculated to be the following reason. Generally, when the positive electrode active material layer is set very thick, local peeling of the positive electrode active material layer is easy to occur (typically, local peeling of the surface layer of the positive electrode active material layer). In addition, when the peel strength between the positive electrode active material layer and the positive electrode substrate is low, interlayer peeling is easy to occur. In contrast, in the positive electrode described in [1] above, since the average thickness of the positive electrode active material layer is less than 35μm and the 180° peel strength between the positive electrode active material layer and the positive electrode substrate is more than 0.6N / mm, the peeling of the positive electrode active material layer is suppressed. In addition, in order to suppress the peeling of the positive electrode active material layer, it is ideal to increase the pressure relative to the positive electrode active material layer in the manufacturing process as described above so that the positive electrode active material layer and the positive electrode substrate are firmly bonded. However, it is considered that when the elongation at break of the positive electrode substrate is large, strain of the positive electrode substrate caused by pressing under high pressure is likely to occur, thereby reducing the foil-passing property of the positive electrode. In contrast, it is considered that in the positive electrode described in [1] above, since the elongation at break of the positive electrode substrate is small, 3.8% or less, strain is unlikely to occur even when pressing under high pressure, and the foil-passing property is high.
[0026] The “elongation at break” is a value measured in accordance with JIS-Z-2241 (2011) “Methods for tensile testing of metallic materials”.
[0027] The “average thickness of the positive electrode active material layer” and the “average thickness of the positive electrode” described later are the average values of the thickness measurements at any 10 locations. When positive electrode active material layers are provided on both sides of the positive electrode substrate, that is, when the positive electrode has two positive electrode active material layers, the average thickness of the positive electrode active material layer refers to the average thickness of one positive electrode active material layer. When the positive electrode has two positive electrode active material layers, at least one of the positive electrode active material layers has the above average thickness. However, it is preferred that both positive electrode active material layers have the above average thickness.
[0028] "180° peel strength" is a value measured in accordance with JIS-Z-0237 (2009) "Adhesive Tape·Adhesive Sheet Test Method". Specifically, a double-sided tape with sufficient adhesive strength is used to fix the surface of the positive electrode active material layer of the measured positive electrode on the measuring plate, and a digital dynamometer DS2 is used as a measuring instrument. Under the condition of 25°C, the peeling angle is set to 180°, and the strength of the positive electrode substrate when it is peeled off from the positive electrode active material layer fixed on the measuring plate at a peeling speed of 100mm / min is measured. In the case where positive electrode active material layers are respectively provided on both sides of the positive electrode substrate, that is, in the case where the positive electrode has two positive electrode active material layers, the average thickness of at least one of the positive electrode active material layers is 35μm or less, and the 180° peel strength between the positive electrode active material layer and the positive electrode substrate is 0.6N / mm or more. However, it is preferred that the average thickness of the two positive electrode active material layers is 35μm or less, and the 180° peel strength between each positive electrode active material layer and the positive electrode substrate is 0.6N / mm or more.
[0029] [2] In the positive electrode described in [1] above, the average thickness is 80 μm or less. In the positive electrode described in [2] above, by reducing the thickness of the positive electrode itself, the peeling of the positive electrode active material layer is further suppressed. In addition, even if the thickness of the positive electrode itself is thin, since the elongation at break of the positive electrode substrate is 3.8% or less, it is difficult to generate strain when pressed under high pressure, and high foil permeability can be exerted.
[0030] [3] In the positive electrode described in [1] or [2] above, the density of the positive electrode active material layer may be 2.6 g / cm 3 In the positive electrode described in [3] above, when the density of the positive electrode active material layer is high, the adhesion between the particles constituting the positive electrode active material layer and the adhesion between the positive electrode active material layer and the positive electrode base layer are improved, thereby further suppressing the peeling of the positive electrode active material layer.
[0031] The “density of the positive electrode active material layer” is a value obtained from the average thickness, area, and mass of the positive electrode active material layer. That is, the density of the positive electrode active material layer is an apparent density.
[0032] [4] Another aspect of the present invention relates to a non-aqueous electrolyte storage element comprising the positive electrode according to any one of [1] to [3] above. The non-aqueous electrolyte storage element according to [4] above uses a positive electrode in which the peeling of the positive electrode active material layer is suppressed and the foil permeability is high, so the defect rate in the winding process is low and various performances as a storage element are excellent.
[0033] Hereinafter, a positive electrode, a method for manufacturing the same, a nonaqueous electrolyte storage element, a storage device, a method for manufacturing the nonaqueous electrolyte storage element, and other embodiments according to an embodiment of the present invention will be described in detail. It should be noted that the names of the components (constituent elements) used in each embodiment are sometimes different from the names of the components (constituent elements) used in the background art.
[0034] <Positive electrode>
[0035] The positive electrode involved in one embodiment of the present invention comprises a positive electrode substrate and a positive electrode active material layer stacked on the positive electrode substrate directly or via an intermediate layer. The positive electrode is a positive electrode for a non-aqueous electrolyte storage element. The positive electrode can be used for a wound electrode body or a stacked electrode body. The positive electrode is particularly suitable for a wound electrode body from the viewpoint of fully utilizing the advantages of the positive electrode active material layer being suppressed from peeling off and the high foil permeability during the manufacture of the electrode body. The positive electrode may also have a strip shape, for example. In the positive electrode, the positive electrode active material layer may be arranged only on one surface of the positive electrode substrate, or may be arranged on both surfaces of the positive electrode substrate.
[0036] The positive electrode substrate has electrical conductivity. Whether it has "electrical conductivity" is determined by the volume resistivity 10 measured in accordance with JIS-H-0505 (1975). -2 Ω·cm is used as a threshold value for determination. The shape of the positive electrode substrate is usually a sheet or plate, and is preferably a sheet-shaped foil formed by thinly beating it.
[0037] The positive electrode substrate contains metallic aluminum. That is, the material of the positive electrode substrate is usually any one of pure aluminum and aluminum alloy. From the viewpoint of strength, the material of the positive electrode substrate is preferably an aluminum alloy. The content of metallic aluminum in the positive electrode substrate can be, for example, 80% to 100% by mass, or can be 90% or more by mass or 95% or more by mass.
[0038] The upper limit of the elongation at break of the positive electrode substrate is 3.8%, preferably 3.7%, more preferably 3.6%, and further preferably 3.5%. By making the elongation at break of the positive electrode substrate below the above upper limit, it is not easy to produce strain when pressing under high pressure, etc., and the foil permeability is improved. The lower limit of the elongation at break of the positive electrode substrate can be 1.0%, 2.0%, 2.5%, 3.0%, 3.2%, 3.4% or 3.5%. The elongation at break of the positive electrode substrate can be above any of the above lower limits and below any of the above upper limits. The elongation at break of the positive electrode substrate adopts the value of the extension direction or long side direction of the positive electrode substrate.
[0039] As the positive electrode substrate, commercially available foils of pure aluminum or aluminum alloys such as A1000 series (e.g., A1100), A3000 series, and A1N30 series, which have an elongation at break of 3.8% or less, as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006), can be used. The material and thickness of the positive electrode substrate affect the elongation at break.
[0040] The average thickness of the positive electrode substrate is preferably 3μm to 50μm, more preferably 5μm to 40μm, further preferably 8μm to 30μm, and particularly preferably 10μm to 25μm. The average thickness of the positive electrode substrate can be 20μm or less, or 16μm or less (for example, 10μm to 16μm). By making the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be improved, and the energy density per unit volume of the non-aqueous electrolyte storage element can be improved. The average thickness of the above-mentioned positive electrode substrate can be above any of the above-mentioned lower limits and below any of the above-mentioned upper limits. The "average thickness" of the positive electrode substrate and the negative electrode substrate described later refers to the value obtained by dividing the punching mass when punching a substrate of a specified area by the true density of the substrate and the punching area.
[0041] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer reduces the contact resistance between the positive electrode substrate and the positive electrode active material layer by containing a conductive agent such as carbon particles. The structure of the intermediate layer is not particularly limited, and for example, it contains a binder and a conductive agent.
[0042] The positive electrode active material layer contains a positive electrode active material and may contain any components such as a conductive agent, a binder, a thickener, and a filler as necessary.
[0043] As the positive electrode active material, it can be appropriately selected from known positive electrode active materials. As the positive electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. As the positive electrode active material, for example, lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel crystal structure, polyanion compounds, chalcogen compounds, sulfur, etc. can be cited. As lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, for example, Li[Li x Ni (1-x) ]O2(0≤≤x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β) etc. As lithium transition metal composite oxides having a spinel crystal structure, Li x Mn2O4、Li x Ni γ Mn (2-γ) O4, etc. As polyanion compounds, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. can be mentioned. As chalcogenides, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be mentioned. The atoms or polyanions in these materials can be partially replaced by atoms or anionic substances composed of other elements. The surfaces of these materials can also be coated with other materials. In the positive electrode active material layer, one of these materials can be used alone, or two or more can be mixed and used.
[0044] As the positive electrode active material, a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure is preferred. In the lithium transition metal composite oxide having an α-NaFeO2 type crystal structure, it is preferred to contain at least one of nickel, cobalt and manganese, and more preferably to contain nickel, cobalt and manganese.
[0045] The positive electrode active material is generally a particle (powder). The average particle size of the positive electrode active material is preferably 0.1 μm to 20 μm, for example. By making the average particle size of the positive electrode active material above the above lower limit, the manufacture or handling of the positive electrode active material is facilitated. By making the average particle size of the positive electrode active material below the above upper limit, the electronic conductivity of the positive electrode active material layer is improved. It should be noted that when a composite of the positive electrode active material and other materials is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. "Average particle size" refers to the particle size distribution measured by laser diffraction and scattering method on a dilution obtained by diluting the particles in a solvent in accordance with JIS-Z-8825 (2013), and the volume standard cumulative distribution calculated according to JIS-Z-8819-2 (2001) is 50%.
[0046] In order to obtain a powder of a predetermined particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, a method using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow jet mill, or a sieve can be cited. During pulverization, wet pulverization in which organic solvents such as water or hexane coexist can also be used. As a classification method, a sieve, a wind classifier, etc. can be used, and can be used together with a dry method or a wet method as needed.
[0047] The BET specific surface area of the positive electrode active material is preferably 0.5 m 2 / g~3.0m 2 / g, more preferably 1.0m 2 / g~2.0m 2 / g, more preferably 1.2m 2 / g~1.8m 2 / g, and more preferably 1.4m 2 / g~1.6m 2 / g. When the BET specific surface area of the positive electrode active material is small, that is, when the BET specific surface area of the positive electrode active material is below the above-mentioned upper limit, the binder is difficult to be adsorbed into the pores of the positive electrode active material, and the binder is easily present between the positive electrode active material particles, so the peeling of the positive electrode active material layer can be more fully suppressed. When the BET specific surface area of the positive electrode active material is below the above-mentioned upper limit, even if the content of the binder in the positive electrode active material layer is small (for example, less than 6% by mass, typically less than 4% by mass), a positive electrode with a large 180° peel strength between the positive electrode active material layer and the positive electrode substrate can be achieved. On the other hand, by making the BET specific surface area of the positive electrode active material above the above-mentioned lower limit, the contact area between the positive electrode active material and the non-aqueous electrolyte can be fully ensured, and the charge and discharge performance can be improved. The BET specific surface area of the above-mentioned positive electrode active material can be above any of the above-mentioned lower limits and below any of the above-mentioned upper limits.
[0048] The BET specific surface area of the positive electrode active material is determined by the following method. The surface area is measured by a multi-point nitrogen adsorption method in the relative pressure range of 0.05 to 0.2 with respect to the positive electrode active material. The obtained surface area (nitrogen adsorption amount: m 2 ) divided by the mass of the positive electrode active material (g), and the BET specific surface area (m 2 / g).
[0049] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% to 99% by mass, more preferably 70% to 98% by mass, and further preferably 80% to 95% by mass. In some embodiments, the content of the positive electrode active material can be 85% by mass or more, or 90% by mass or more (e.g., 92% by mass or more). By setting the content of the positive electrode active material to the above range, the high energy density and manufacturability of the positive electrode active material layer can be taken into account.
[0050] The conductive agent is not particularly limited as long as it is a material with conductivity. Examples of such conductive agents include carbon materials, metals, conductive ceramics, etc. Examples of carbon materials include graphite, non-graphite carbon, graphene-based carbon, etc. Examples of non-graphite carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, etc. Examples of carbon black include furnace black, acetylene black, Ketjen black, etc. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, etc. Examples of the shape of the conductive agent include powder, fiber, etc. Examples of the conductive agent include one of these materials alone, or a mixture of two or more. In addition, these materials may be used in combination. For example, a material obtained by combining carbon black with CNT may also be used. Among these, carbon black is preferred from the viewpoint of electrical conductivity and coating properties, and acetylene black is preferred.
[0051] The content of the conductive agent in the positive electrode active material layer is preferably 1% to 10% by mass, and more preferably 3% to 9% by mass. When the content of the conductive agent is within the above range, the energy density of the nonaqueous electrolyte storage device can be increased.
[0052] As adhesives, for example, there can be mentioned thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0053] The content of the binder in the positive electrode active material layer is preferably 1% to 10% by mass, and more preferably 3% to 9% by mass. In some embodiments, the content of the binder may be 7% by mass or less, or 5% by mass or less (e.g., 3.5% by mass or less). By making the content of the binder within the above range, the positive electrode active material can be stably maintained, further suppressing the peeling of the positive electrode active material layer.
[0054] As thickeners, for example, polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose can be cited. In the case where the thickener has a functional group that reacts with lithium or the like, the functional group can be deactivated in advance by methylation or the like. When a thickener is used, the content of the thickener in the positive electrode active material layer is preferably 5% by mass or less, and more preferably 1% by mass or less. The technology disclosed herein is preferably implemented in a manner that does not contain a thickener in the positive electrode active material layer.
[0055] The filler is not particularly limited. As fillers, polyolefins such as polypropylene and polyethylene can be cited; inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide and aluminosilicate; hydroxides such as magnesium hydroxide, calcium hydroxide, aluminum hydroxide; carbonates such as calcium carbonate; insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate; nitrides such as aluminum nitride and silicon nitride; talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica and other materials from mineral resources or their man-made products. When a filler is used, the content of the filler in the positive electrode active material layer is less than 5% by mass, and more preferably less than 1% by mass. The technology disclosed herein is preferably implemented in a manner that does not contain a filler in the positive electrode active material layer.
[0056] The positive electrode active material layer may also contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0057] The upper limit of the average thickness of the positive electrode active material layer is 35 μm, preferably 34 μm, more preferably 33 μm, and further preferably 32 μm. By making the average thickness of the positive electrode active material layer below the above upper limit, partial peeling of the positive electrode active material layer is suppressed. The lower limit of the average thickness of the positive electrode active material layer is, for example, 10 μm, more preferably 20 μm, further preferably 25 μm, and further preferably 30 μm. By making the average thickness of the positive electrode active material layer above the above lower limit, the capacity of the obtained non-aqueous electrolyte storage element can be increased. The average thickness of the positive electrode active material layer can be above any of the above lower limits and below any of the above upper limits. The average thickness of the positive electrode active material layer can be adjusted according to the amount of the positive electrode mixture paste applied later, the pressing pressure during pressing, etc.
[0058] The lower limit of the 180° peel strength between the positive electrode active material layer and the positive electrode substrate is 0.6N / mm, preferably 0.7N / mm, more preferably 0.8N / mm, further preferably 0.9N / mm, and further preferably 1.0N / mm. By making the 180° peel strength between the positive electrode active material layer and the positive electrode substrate above the above lower limit, the adhesion between the positive electrode active material layer and the positive electrode substrate is improved, and the peeling of the positive electrode active material layer is suppressed. The upper limit of the 180° peel strength can be, for example, 3.0N / mm, 2.0N / mm, 1.5N / mm or 1.2N / mm. By making the above 180° peel strength below the above upper limit, the productivity of the positive electrode can be improved. The above 180° peel strength can be above any of the above lower limits and below any of the above upper limits. The above 180° peel strength can be adjusted according to the type and content of each component such as the binder contained in the positive electrode active material layer, the pressing pressure during pressing, etc.
[0059] The density of the positive electrode active material layer can be 2.0 g / cm 3 ~4.0g / cm 3 , preferably 2.6 g / cm 3 ~3.5g / cm 3 , more preferably 2.7 g / cm 3 ~3.0g / cm 3 The upper limit of this density can be 2.9 g / cm3 , or 2.8 g / cm 3 . By making the density of the positive electrode active material layer above the above lower limit, the energy density of the positive electrode active material layer can be increased. In addition, the effect of improving the foil permeability brought about by making the elongation at break of the positive electrode substrate below 3.8% can be more effectively exerted. On the other hand, for the positive electrode active material layer having a density below the above upper limit, peeling is further suppressed, and in addition, it can be efficiently manufactured by a general pressing device or the like. The density of the positive electrode active material layer can be adjusted according to the type, content and shape of each component such as the positive electrode active material contained in the positive electrode active material layer, the pressing pressure during pressing, etc.
[0060] The average thickness of the positive electrode (average thickness of the entire positive electrode) may be, for example, 10 μm to 200 μm, preferably 30 μm to 150 μm, more preferably 50 μm to 100 μm, and further preferably 70 μm to 80 μm. By making the average thickness of the positive electrode below the upper limit, the peeling of the positive electrode active material layer is further suppressed. On the other hand, by making the average thickness of the positive electrode above the lower limit, there is a tendency for the strength to be improved and the foil permeability to be improved.
[0061] <Positive electrode manufacturing method>
[0062] The positive electrode according to one embodiment of the present invention is manufactured by, for example, applying a positive electrode mixture paste directly or via an intermediate layer on a positive electrode substrate and drying it, forming an unpressed positive electrode active material layer, and pressing the unpressed positive electrode having the unpressed positive electrode active material layer. The positive electrode mixture paste contains the positive electrode active material and the conductive agent, binder, and other components constituting the positive electrode active material layer as arbitrary components. The positive electrode mixture paste usually further contains a dispersion medium.
[0063] The pressing is performed by applying pressure to the surface of the unpressed positive electrode active material layer. The pressing can be performed by a conventionally known pressing device such as a roller press. By increasing the pressure during the pressing, the 180° peel strength between the positive electrode active material layer and the positive electrode substrate can be increased.
[0064] <Non-aqueous electrolyte energy storage device>
[0065] A nonaqueous electrolyte storage element (hereinafter also referred to as "storage element") according to one embodiment of the present invention comprises: an electrode body having a positive electrode, a negative electrode and a separator; a nonaqueous electrolyte; and a container for accommodating the electrode body and the nonaqueous electrolyte. The electrode body is generally a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked via a separator, or a wound type in which a positive electrode and a negative electrode are wound in a state in which the positive electrode and the negative electrode are stacked via a separator. The nonaqueous electrolyte exists in a state impregnated in the positive electrode, the negative electrode and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter referred to as "secondary battery") is described.
[0066] (positive electrode)
[0067] The positive electrode included in the nonaqueous electrolyte electricity storage element is the positive electrode according to the above-mentioned embodiment of the present invention.
[0068] (negative electrode)
[0069] The negative electrode comprises a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The structure of the intermediate layer is not particularly limited and can be selected from the structures exemplified in the above-mentioned positive electrode.
[0070] The negative electrode substrate has conductivity. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel, aluminum, or their alloys, carbon materials, etc. can be used. Among them, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.
[0071] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By making the average thickness of the negative electrode substrate within the above range, the strength of the negative electrode substrate can be improved, and the energy density per unit volume of the non-aqueous electrolyte storage element can be improved.
[0072] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains any component such as a conductive agent, a binder, a thickener, a filler, etc. as needed. The conductive agent, the binder, the thickener, the filler, etc. can be selected from the materials exemplified in the above-mentioned positive electrode. The negative electrode active material layer is usually formed by a so-called negative electrode mixture containing a negative electrode active material. The negative electrode active material layer can also be a layer substantially composed only of a negative electrode active material such as metal Li.
[0073] The negative electrode active material layer may also contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.
[0074] The negative electrode active material can be appropriately selected from known negative electrode active materials. Generally, materials that can absorb and release lithium ions can be used as negative electrode active materials for lithium ion secondary batteries. Examples of negative electrode active materials include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO2, TiNb2O7 and other titanium-containing oxides; polyphosphate compounds; silicon carbide; carbon materials such as graphite and non-graphite carbon (graphitizable carbon or non-graphitizable carbon). Among these materials, graphite and non-graphite carbon are preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used.
[0075] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before or after charge / discharge or in a discharged state. 002 ) is a carbon material having a diameter of 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. From the perspective of obtaining a material with stable physical properties, artificial graphite is preferred.
[0076] “Non-graphite carbon” refers to the average lattice spacing (d ) of the (002) plane determined by X-ray diffraction before charge / discharge or in the discharged state. 002 ) is a carbon material having a diameter of 0.34 nm to 0.42 nm. Examples of non-graphite carbon include hard graphite carbon and easy graphite carbon. Examples of non-graphite carbon include materials derived from resins, petroleum asphalt or materials derived from petroleum asphalt, petroleum coke or materials derived from petroleum coke, materials derived from plants, and materials derived from alcohols.
[0077] Here, the "discharge state" refers to a state in which lithium ions that can be absorbed and released during charge and discharge are fully released from the carbonaceous material as the negative electrode active material. For example, in a half-cell having a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metal Li as a counter electrode, the open circuit voltage is 1.2V or more.
[0078] "Difficult to graphitize carbon" refers to the above-mentioned 002It is a carbon material with a diameter of 0.36nm to 0.42nm.
[0079] "Easily graphitizable carbon" refers to the above-mentioned 002 A carbon material having a diameter of 0.34 nm or more and less than 0.36 nm.
[0080] The negative electrode active material is generally a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm to 100 μm. When the negative electrode active material is a carbon material, a titanium oxide or a polyphosphate compound, its average particle size can also be 1 μm to 100 μm. When the negative electrode active material is Si, Sn, Si oxide or Sn oxide, etc., its average particle size can also be 1 nm to 1 μm. By setting the average particle size of the negative electrode active material to above the above lower limit, it is easy to manufacture or handle the negative electrode active material. By making the average particle size of the negative electrode active material below the above upper limit, the electronic conductivity of the negative electrode active material layer is improved. In order to obtain a powder of a specified particle size, a pulverizer, a classifier, etc. can be used. The pulverization method and the classification method can be selected from the methods exemplified in the above-mentioned positive electrode. When the negative electrode active material is a metal such as metal Li, the negative electrode active material can also be in the form of foil.
[0081] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% to 99% by mass, and more preferably 90% to 98% by mass. By making the content of the negative electrode active material within the above range, it is possible to take into account both the high energy density and the manufacturability of the negative electrode active material layer. When the negative electrode active material is metallic Li, the content of the negative electrode active material in the negative electrode active material layer may be 99% by mass or more, or may be 100% by mass.
[0082] In the case of using a conductive agent in the negative electrode active material layer, the content of the conductive agent relative to the negative electrode active material layer may be 10% by mass or less, preferably 8% by mass or less or 3% by mass or less. The technology disclosed herein may preferably be implemented in a manner that does not contain a conductive agent in the negative electrode active material layer. In the case of using a binder in the negative electrode active material layer, the content of the binder relative to the negative electrode active material layer is preferably 1% by mass to 10% by mass, and more preferably 2% by mass to 8% by mass. In the case of using a thickener in the negative electrode active material layer, the content of the thickener relative to the negative electrode active material layer may be 0.5% by mass to 8% by mass, and preferably 1% by mass to 6% by mass. In the case of using a filler in the negative electrode active material layer, the content of the filler relative to the negative electrode active material layer may be 8% by mass or less, preferably 5% by mass or less or 1% by mass or less. The technology disclosed in this way is preferably implemented in a manner that does not contain a filler in the negative electrode active material layer.
[0083] (Isolator)
[0084] The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and an adhesive is formed on one or both surfaces of the substrate layer, etc. can be used. As the shape of the substrate layer of the separator, woven fabrics, non-woven fabrics, and porous resin films can be cited. Among these shapes, from the viewpoint of strength, porous resin films are preferred, and from the viewpoint of liquid retention of non-aqueous electrolytes, non-woven fabrics are preferred. As the material of the substrate layer of the separator, from the viewpoint of insulation function, for example, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of anti-oxidative decomposition, polyimides, aromatic polyamides, etc. are preferred. As the substrate layer of the separator, a material composited with these resins can also be used.
[0085] The heat-resistant particles contained in the heat-resistant layer preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 500°C in an air atmosphere at 1 atmosphere pressure, and more preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 800°C. As materials whose mass reduction is below a specified value, inorganic compounds can be cited. As inorganic compounds, for example, oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; insoluble ionic crystals such as calcium fluoride, barium fluoride and barium titanate. Covalent crystals such as silicon and diamond. Materials derived from mineral resources such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or their artificial products. As inorganic compounds, monomers or complexes of these substances can be used alone, or two or more can be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of safety of the nonaqueous electrolyte storage element.
[0086] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and preferably 20% by volume or more from the viewpoint of discharge performance. Here, the "porosity" refers to a value based on volume, and is measured using a mercury porosimeter.
[0087] As a separator, a polymer gel composed of a polymer and a non-aqueous electrolyte can be used. As the polymer, for example, polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyvinylidene fluoride, etc. can be cited. The use of polymer gel can have an effect of suppressing leakage. As a separator, a porous resin film or non-woven fabric as described above can be used together with the polymer gel.
[0088] (Non-aqueous electrolyte)
[0089] As the non-aqueous electrolyte, it can be appropriately selected from known non-aqueous electrolytes. A non-aqueous electrolyte solution can also be used as the non-aqueous electrolyte. The non-aqueous electrolyte solution contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.
[0090] As non-aqueous solvent, it can be appropriately selected from known non-aqueous solvents. Non-aqueous solvents include cyclic carbonate, linear carbonate, carboxylate, phosphoric acid ester, sulfonic acid ester, ether, amide, nitrile, etc. As non-aqueous solvent, a solvent in which a part of the hydrogen atoms contained in these compounds are replaced by halogen atoms can be used.
[0091] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, fluorinated ethylene carbonate (FEC), difluorinated ethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate. Among them, EC is preferred.
[0092] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among them, EMC is preferred.
[0093] As the non-aqueous solvent, preferably a cyclic carbonate or a chain carbonate is used, and more preferably a cyclic carbonate and a chain carbonate are used together. By using a cyclic carbonate, the dissociation of the electrolyte salt can be promoted and the ion conductivity of the non-aqueous electrolyte can be improved. By using a chain carbonate, the viscosity of the non-aqueous electrolyte can be controlled to decrease. When a cyclic carbonate and a chain carbonate are used together, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate: chain carbonate) is, for example, preferably in the range of 5:95 to 50:50.
[0094] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, Among them, lithium salts are preferred.
[0095] As lithium salts, inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, LiN(SO2F)2, lithium oxalate salts such as lithium di(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), difluorobis(oxalate)phosphate (LiFOP), lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, LiC(SO2C2F5)3, etc. can be cited. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.
[0096] The content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / dm 3 ~2.5mol / dm 3 , more preferably 0.3 mol / dm 3 ~2.0mol / dm 3 , more preferably 0.5 mol / dm 3 ~1.7mol / dm 3 , particularly preferably 0.7 mol / dm 3 ~1.5mol / dm 3 By setting the content of the electrolyte salt to be within the above range, the ion conductivity of the non-aqueous electrolyte can be improved.
[0097] In addition to the non-aqueous solvent and the electrolyte salt, the non-aqueous electrolyte may also contain additives. Examples of additives include halogenated carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC); lithium oxalate salts such as lithium di(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and difluorobis(oxalate)phosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); biphenyl, alkylbiphenyl, terphenyl, partial hydride of terphenyl, cyclohexylbenzene, , tert-butylbenzene, tert-amylbenzene, diphenyl ether, dibenzofuran and other aromatic compounds; 2-fluorobiphenyl, o-cyclohexylfluorobenzene, p-cyclohexylfluorobenzene and other partial halides of the above aromatic compounds; 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, 3,5-difluoroanisole and other halogenated anisole compounds; vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, succinic anhydride, glutaric anhydride , maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; vinyl sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, vinyl sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiapentane) , 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridine disulfide, 1,3-propylene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, monofluorolithium phosphate, difluorolithium phosphate, etc. These additives may be used alone or in combination of two or more.
[0098] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% to 10% by mass, more preferably 0.1% to 7% by mass, further preferably 0.2% to 5% by mass, and particularly preferably 0.3% to 3% by mass, relative to the overall mass of the non-aqueous electrolyte. By making the content of the additive within the above range, the capacity maintenance performance or cycle performance after high temperature storage can be improved, and the safety can be further improved.
[0099] A solid electrolyte may be used as the non-aqueous electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.
[0100] The solid electrolyte can be selected from any material that has ion conductivity and is solid at room temperature (e.g., 15° C. to 25° C.), such as lithium, sodium, and calcium. Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes.
[0101] As sulfide solid electrolytes, in the case of lithium ion secondary batteries, for example, Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 wait.
[0102] The shape of the nonaqueous electrolyte storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, and button batteries.
[0103] Figure 1 A non-aqueous electrolyte storage element 1 is shown as an example of a square battery. It should be noted that this figure is also a view of the inside of a container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a square container 3. The positive electrode is electrically connected to a positive terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative terminal 5 via a negative electrode lead 51.
[0104] <Electricity storage device>
[0105] The non-aqueous electrolyte storage element of this embodiment can be used as a storage unit (battery module) composed of a plurality of non-aqueous electrolyte storage elements and can be mounted on a power supply for an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc., a personal computer, a communication terminal, etc. In this case, the technology of the present invention can be applied to at least one non-aqueous electrolyte storage element contained in the storage unit.
[0106] Figure 2 , an example of a power storage device 30 is shown in which a power storage unit 20 formed by a collection of two or more electrically connected non-aqueous electrolyte power storage elements 1 is further collected. The power storage device 30 may also include a bus bar (not shown) that electrically connects the two or more non-aqueous electrolyte power storage elements 1, a bus bar (not shown) that electrically connects the two or more power storage units 20, etc. The power storage unit 20 or the power storage device 30 may also include a state monitoring device (not shown) that monitors the state of the one or more non-aqueous electrolyte power storage elements.
[0107] <Method for producing non-aqueous electrolyte storage element>
[0108] The manufacturing method of the non-aqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The manufacturing method, for example, comprises: a step of preparing an electrode body, a step of preparing a non-aqueous electrolyte, and a step of accommodating the electrode body and the non-aqueous electrolyte in a container. The step of preparing the electrode body comprises: a step of preparing a positive electrode and a negative electrode, and a step of forming an electrode body by stacking or winding the positive electrode and the negative electrode via a separator.
[0109] The method of storing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte is used as the non-aqueous electrolyte, the non-aqueous electrolyte is injected from an injection port formed in the container and then the injection port is sealed.
[0110] <Other embodiments>
[0111] It should be noted that the nonaqueous electrolyte storage element of the present invention is not limited to the above-mentioned embodiment, and various changes can be made within the scope of the gist of the present invention. For example, the structure of other embodiments can be added to the structure of one embodiment, and in addition, a part of the structure of one embodiment can be replaced with the structure of other embodiments or known technology. Furthermore, a part of the structure of one embodiment can be deleted. In addition, known technology can be added to the structure of one embodiment.
[0112] In the above embodiment, the case where the nonaqueous electrolyte storage element is used for a rechargeable nonaqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) is described, but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to capacitors such as various secondary batteries, double-layer capacitors, or lithium ion capacitors.
[0113] In the above embodiment, the electrode body is described as a stacked positive electrode and a negative electrode with a separator interposed therebetween, but the electrode body may not include a separator. For example, the positive electrode and the negative electrode may be directly connected with a non-conductive layer formed on the active material layer of the positive electrode or the negative electrode.
[0114] Example
[0115] Hereinafter, the present invention will be further specifically described by way of examples, but the present invention is not limited to the following examples.
[0116] [Example 1]
[0117] (Production of positive electrode)
[0118] Using LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(BET specific surface area: 1.52m 2 / g) as the positive electrode active material, carbon black as the conductive agent, and polyvinylidene fluoride (PVDF) as the binder. A proper amount of N-methyl-pyrrolidone (NMP) is added to a mixture of the positive electrode active material, carbon black and PVDF in a mass ratio of 94:3:3 (solid content conversion) to adjust the viscosity and obtain a positive electrode mixture paste. The positive electrode mixture paste is coated on both sides of an aluminum foil (A1100, average thickness 15μm, elongation at break 3.5%) serving as a positive electrode substrate and dried to provide an unpressed positive electrode active material layer. Then, roller pressing is performed to obtain a layer with an average thickness of 31.5μm and a density of 2.73g / cm on each side of the positive electrode substrate. 3 The positive electrode strip of Example 1 has a positive electrode active material layer of 100 μm and an average thickness of 78 μm. The 180° peel strength between the positive electrode active material layer and the positive electrode substrate in the positive electrode of Example 1 is 1.04 N / mm.
[0119] [Comparative Examples 1 to 5]
[0120] As the positive electrode substrate, an aluminum foil having the average thickness and elongation at break described in Table 1 was used, and the pressure of the roller press was adjusted so that the average thickness and density of the positive electrode active material layer and the average thickness of the positive electrode became as described in Table 1. The same procedure as in Example 1 was performed to obtain each positive electrode of Comparative Examples 1 to 5. The 180° peel strength between the positive electrode active material layer and the positive electrode substrate in each positive electrode of Comparative Examples 1 to 5 is shown in Table 1.
[0121] [evaluate]
[0122] (Slippage of the positive electrode active material layer)
[0123] The positive electrodes of Example 1 and Comparative Examples 1 to 5 were cut with a Thomson cutter (20 mm × 50 mm), and the number of chips produced was observed with an optical microscope to confirm whether the positive electrode active material layer had slipped. Here, each positive electrode of the embodiment and comparative example was cut with a width of 100 mm using a Thomson cutter, and the number of chips produced was counted. The case where the number of chips was less than 3 was evaluated as (A), and the case where the number of chips exceeded 3 was evaluated as (C). The results are shown in Table 1.
[0124] [evaluate]
[0125] (Foil penetration)
[0126] The foil-through property of each positive electrode obtained in Example 1 and Comparative Examples 1 to 5 was evaluated according to the following procedure. The positive electrode and the negative electrode were wound with a separator using a winding device to produce a wound electrode body. In the negative electrode, a negative electrode active material layer containing non-graphitizable carbon as a negative electrode active material was provided on both sides of a strip-shaped copper foil as a negative electrode substrate. A strip-shaped porous resin film made of polyolefin was used as the separator. Using each positive electrode of the embodiment and the comparative example, 1,000 electrode bodies were produced, and the number of defective electrode bodies (defective number) was counted. It should be noted that when the positive electrode, the negative electrode and the separator are wound, the case where the positive electrode meanders and the position of the positive electrode in the width direction of the electrode body is offset is judged as defective. The case where the number of defects is 1 or less is evaluated as high foil-through property (A), the case where the number of defects is 2 to 9 is evaluated as low foil-through property (B), and the case where the number of defects is 10 or more is evaluated as very low foil-through property (C). The results are shown in Tables 1 and Figure 3 . Figure 3 This is a graph showing the relationship between the elongation at break of the positive electrode substrate and the number of defects in the winding step.
[0127] [Table 1]
[0128]
[0129] In each positive electrode of Comparative Examples 3 to 5, the average thickness of the positive electrode active material layer exceeds 35μm, and the peel strength (180° peel strength between the positive electrode active material layer and the positive electrode substrate) is also less than 0.6N / mm, which makes it easy for the positive electrode active material layer to peel off. In each positive electrode of Comparative Examples 1 and 2, the average thickness of the positive electrode active material layer is less than 35μm, and the peel strength is more than 0.6N / mm, which can suppress the peeling of the positive electrode active material layer. However, in each positive electrode of Comparative Examples 1 and 2, a positive electrode substrate with a breaking elongation greater than 3.8% is used, and the number of defects in the winding process is large, and the foil passability is low or very low. In contrast, in the positive electrode of Example 1, in which the average thickness of the positive electrode active material layer is less than 35μm, the peel strength is more than 0.6N / mm, and the breaking elongation of the positive electrode substrate is less than 3.8%, the peeling of the positive electrode active material layer is suppressed, the number of defects in the winding process is small, and the foil passability is high.
[0130] It should be explained, such as Figure 3As shown, regardless of the average thickness and peel strength of the positive electrode active material layer, the smaller the elongation at break of the positive electrode substrate, the fewer the number of defects in the winding process. Among them, in the case of Example 1 and Comparative Examples 1 and 2, where the average thickness of the positive electrode active material layer is less than 35 μm and the peel strength is more than 0.6 N / mm, the reduction rate (slope) of the number of defects relative to the change in elongation at break is large compared with Comparative Examples 3 to 5. It can be confirmed that when the average thickness of the positive electrode active material layer is less than 35 μm and the peel strength is more than 0.6 N / mm, the improvement in foil permeability brought about by the elongation at break of less than 3.8% is particularly effective.
[0131] Industrial Applicability
[0132] The present invention can be applied to a non-aqueous electrolyte storage element used as a power source for electronic devices such as personal computers and communication terminals, and automobiles, and a positive electrode included therein.
[0133] Explanation of symbols
[0134] 1 Non-aqueous electrolyte storage element
[0135] 2 Electrode body
[0136] 3 Container
[0137] 4 Positive terminal
[0138] 41 Positive wire
[0139] 5 Negative terminal
[0140] 51 Negative lead
[0141] 20 Storage unit
[0142] 30 Power storage device
Claims
1. A positive electrode for a non-aqueous electrolyte storage element, comprising a positive electrode substrate and a positive electrode active material layer, wherein the positive electrode substrate contains metal aluminum, and the positive electrode active material layer is stacked on the positive electrode substrate; The elongation at break of the positive electrode substrate is 3.8% or less, The average thickness of the positive electrode active material layer is 35 μm or less. The 180° peel strength between the positive electrode active material layer and the positive electrode substrate is greater than or equal to 0.6 N / mm. 2 . The positive electrode according to claim 1 , which has an average thickness of 80 μm or less.
3. The positive electrode according to claim 1 or 2, wherein The density of the positive electrode active material layer is 2.6 g / cm 3 above. 4 . A non-aqueous electrolyte storage element comprising the positive electrode according to claim 1 .
Citation Information
Patent Citations
Electricity storage element
JP2017201589A